Meningkatkan Hasil Belajaran PKn Tema 8 Dengan Penerapan Model Pembelajaran Kooperatif Tipe the Power Of Two Pada Siswa Kelas III SDN 006 Bukit Kapur Dumai - Dewi, Sucitra (Jurnal Pendidikan Tuntas, 2025)
his research is motivated by findings among third-grade students at SDN 006 Bukit Kapur, Dumai, during Civics (PKN) lessons on Theme 8, Subtheme "I am a Scout" (Aku Anggota Pramuka). It was observed that 52% of students had not yet reached the Minimum Mastery Criterion (KKM), with only 48% achieving passing scores, categorizing the results as poor. In addition to low learning outcomes, the quality of the instructional process was also suboptimal. Consequently, improvements in the learning process are necessary to enhance student competence.The objective of this study is to improve student achievement in Civics Theme 8 by implementing the "The Power of Two" Cooperative Learning Model. The conceptual framework proposed is that if the third-grade teacher at SDN 006 Bukit Kapur utilizes peer discussion media through "The Power of Two" method, learning outcomes will increase. The first cycle was conducted on May 4, 2020, followed by the second cycle for further improvement on May 8, 2020. The results showed a significant increase in achievement among the students. Based on these findings, it can be concluded that applying the "The Power of Two" Cooperative Learning method can improve student learning outcomes in Civics Theme 8, Subtheme "I am a Scout," for third-grade students at SDN 006 Bukit Kapur, Dumai, during the second semester of the 2019/2020 academic year.